INDUSTRIAS FORESTALES DE PRODUCTOS NO MADERABLES: CORCHO, RESINAS, ETC. - Solis Sánchez, W (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Within the whole of the forest industries based on secondary forest products, regarding' in Cork and Resins, reviewing to its more characteristics topics, showing its unequal tendency and the meaning role exercised by both in the European' Cornmunity .
Keywords: Cork; E.E.C.; Marketing; Resins